Visual Quality and Subjective Satisfaction in Ultrathin Descemet Stripping Automated Endothelial Keratoplasty (UT-DSAEK) versus Descemet Membrane Endothelial Keratoplasty (DMEK): A Fellow-Eye Comparison - Torras-Sanvicens, Josep (J Clin Med, 2021)
Background: To analyze objective and subjective visual quality differences between descemet membrane endothelial keratoplasty (DMEK) and ultra-thin descemet stripping automated endothelial keratoplasty (UT-DSAEK) with a paired contralateral-eye design. Methods: A cross-sectional, comparative, and observational case series study between DMEK and UT-DSAEK were presented. Visual acuity, refractive status and corneal quality assessment were compared between both endothelial keratoplasty techniques. The sample consisted of 20 eyes (10 patients) diagnosed with Fuchs endothelial corneal dystrophy. All measurements were performed preoperatively and at six months after surgery. Analyzed data included the measurement of objective scattering index, modulation transfer function, Strehl ratio, and optical quality assessment (OQAS) values. Contrast sensitivity, subjective patient satisfaction, visual acuity, tomography, pachymetry, endothelial cell count, and refraction status were also analyzed. Results: Objective and subjective visual quality variables had similar results among UT-DSAEK and DMEK procedures. Statistically significant differences favoring DMEK against UT-DSAEK were found in endothelial cell density (658.80 ± 139.33 and 1059.00 ± 421.84 cells/mm(2), respectively), pachymetry (621.20 ± 33.74 and 529.70 ± 30.00 µm, respectively), and follow-up (45.50 ± 24.76 and 15.50 ± 8.43 months, respectively). Conclusions: UT-DSAEK and DMEK revealed no differences in terms of objective and subjective visual quality. However, DMEK showed a faster recovery during the follow-up, increased endothelial cell density, lower pachymetry, and a more anatomical posterior keratometry against UT-DSAEK in this case series paired-eye study.